Conceptual triad of «socialization - desocialization - resocialization» in the context of the study of social and educational problems of drug-addicted people - Чернецька, Юлія Іванівна (Pedagogy of Higher and Secondary Education, 2019)
Chernetskaya Yu. I. Conceptual triad of «socialization - desocialization - resocialization» in the context of the study of social and educational problems of drug-addicted people. The article reveals the connection between definitions «socialization», «desocialization» and «resocialization», which presented as a conceptual triad. The scientific basis has been developed and the essential characteristics of the resocialization process of drug-addicted people in terms of social pedagogy have been given. The essence of the key concepts «resocialization», «resocialization of drug-addicted people» has been shown.